Clusters as functioning form of local production systems: theoretically-applied aspects - Yevheniy Kurylyak (Cхід, 2013)
The nature, content and conceptual apparatus of clustering processes, their relationship with the concept of new regionalism are uncovered. The methods of determination and competitive advantages, while creating cluster development enterprises, which constitute its structure, the formation of cluster policy in depressed regions are formulated. The criterias that can be the basis of target selection clusters are adduced. The importance for the formation of industrial cluster atmosphere in the region and humanitarian infrastructure are presented. Original theoretical positions developed within the concept of "new regionalism", based on which we can see the confirmation, that regional development should be based on internal competitive advantages, resources of local economy, and also the cross-sector production under transfer of significant powers of regional authorities are expanded. Herewith the regional authorities reborn in diversified corporation that competes with other regions in creating favorable conditions for economic activities according to the laws of science, information and innovation potentials. Cluster organization usually causes a need to change the internal organization of association members, their goals and mission of forming business groups which are acquired or newly singled by one businesses owner. In innovation field advantages of clustering for firms can be transpired in the formation of specialized agglomerations with a broad geographic network. Firms with location in the center of the cluster must use local assets, borrowing both global resources with the key flows of knowledge, information and skills. Ideally, in the areas of cluster research educational institutions must foothold among the global leaders.